Design of Internal Wire-Based Impedance Matching of Helical Antennas Using an Equivalent Thin-Wire Model - Slobodan V. Savić; Milan M. Ilić; Antonije R. Djordjević (International Journal of Antennas and Propagation)
We propose a novel design of internal impedance matching networks for axial-mode helical antennas. This network comprises a single wire attached to the helix. One of the main challenges when designing an internal matching network is its strong electromagnetic coupling with the antenna. The matching network must hence be designed in the presence of the antenna, which slows down the design process. To overcome this problem, we formulate an equivalent thin-wire model of the complete helix, including the matching wire (matching network) and the dielectric support. This computationally low-demanding model can be analyzed extremely rapidly, yielding accurate results, which are in excellent agreement with alternative numerical solutions and measurements.